1997
DOI: 10.1056/nejm199706263362604
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Neuroradiographic Manifestations of Eastern Equine Encephalitis

Abstract: Eastern equine encephalitis produces focal radiographic signs. The characteristic early involvement of the basal ganglia and thalami distinguish this illness from herpes simplex encephalitis. MRI is a sensitive technique to identify the characteristic early radiographic manifestations of this viral encephalitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
207
5
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(223 citation statements)
references
References 27 publications
9
207
5
2
Order By: Relevance
“…Following an incubation period of 5 to 15 days, infection may progress to systemic then encephalitic disease [5]. Systemic disease presents with headache, fever, malaise, myalgia, nausea, and vomiting.…”
Section: Togaviridaementioning
confidence: 99%
See 1 more Smart Citation
“…Following an incubation period of 5 to 15 days, infection may progress to systemic then encephalitic disease [5]. Systemic disease presents with headache, fever, malaise, myalgia, nausea, and vomiting.…”
Section: Togaviridaementioning
confidence: 99%
“…VEEV, WEEV, and EEEV are all widely distributed in North, Central, and South America. Human infection can progress rapidly to encephalitis, with fatality rates of~1 % in cases of VEEV and WEEV, and 50 % to 75 % in cases of EEEV cases [5,6]. Of the 3, VEEV is considered the most important zoonotic pathogen, with several reported human outbreaks in South and Central Americas, primarily by enzootic VEEV strains [7].…”
Section: Epidemiology Of Encephalitic Arbovirusesmentioning
confidence: 99%
“…However, in some cases, EEE virus crosses the blood-brain barrier and causes a severe, and often fatal, acute encephalitis, which kills 50 to 75% of infected humans and leaves many survivors with serious neurological sequelae. 1,3 It has long been recognized that EEE infection in children tends to have a more rapid onset and to be more severe. Goldfield et al reported that one in eight young children developed fulminant encephalitis and only 1 in 23 had an inapparent infection.…”
mentioning
confidence: 99%
“…This pattern is similar to that seen in ADEM. The presence of neutrophils rather than lymphocytes, as the predominant cell type, occurs frequently in patients with West Nile virus (WNV) neuroinvasive disease [50], and tick borne encephalitis virus [51], and can also occur with Eastern equine encephalitis [52].…”
Section: Viral Encephalitismentioning
confidence: 99%